Regional anesthesia practice in Greece: A census report - Argyra, Erifili; Moka, Eleni; Staikou, Chryssoula; Vadalouca, Athina; Raftopoulos, Vasilios; Stavropoulou, Evmorfia; Gambopoulou, Zoi; Siafaka, Ioanna (My University, 2015)
Background and Aims: Regional anesthesia (RA) techniques (central neuraxial and peripheral nerve blocks [CNBs and PNBs]) are well-established anesthesia/analgesia modalities. However, information on their nationwide use is sparse. The aim of the survey was to assess the utility of RA techniques in Greece, during 2011. Materials and Methods: A nationwide, cross-sectional descriptive survey was conducted (March to June, 2012), using a structured questionnaire that was sent to 128 Greek Anesthesia Departments. Results: Sixty-six completed questionnaires (response rate 51.56%) were analyzed. The data corresponded to 187,703 operations and represented all hospital categories and geographical regions of Greece. On the whole, RA was used in 45.5% of performed surgical procedures (85,386/187,703). Spinal anesthesia was the technique of choice (51.9% of all RA techniques), mostly preferred in orthopedics (44.8%). Epidural anesthesia/analgesia (application rate of 23.2%), was mostly used in obstetrics and gynecology (50.4%). Combined spinal-epidural and PNBs were less commonly instituted (11.24% and 13.64% of all RA techniques, respectively). Most PNBs (78.5%) were performed with a neurostimulator, while elicitation of paresthesia was used in 16% of the cases. Conversely, ultrasound guidance was quite limited (5%). The vast majority of consultant anesthesologists (94.49%) were familiar with CNBs, whereas only 46.4% were familiar with PNBs. The main reported limitations to RA application were lack of equipment (58.23%) and inadequate education/training (49.29%). Conclusion: Regional modalities were routinely used by Greek anesthesiologists during 2011. Neuraxial blocks, especially spinal anesthesia, were preferred over PNBs. The underutilization of certain RA techniques was attributed to lack of equipment and inadequate training.
Keywords: Central neuraxial blocks; Epidural technique; Peripheral nerve blocks; Regional anesthesia; Spinal technique